Ciclo de la Mancha Amarilla o Bronceada del Trigo (Triticum aestivum) - Rollhaiser, Ignacio Nahuel; Pérez, Alejandro Andrés; Pinotti, Carlos Daniel; Fessia, Alfredo Juan; Cordes, Guillermo Gabriel; Muñoz, Julio O. (UNC-FCA-Fitopatología, 2019)
Notas de fitopatología Nº 3